Systematic review and network meta-analysis on the efficacy and safety of parmacotherapy for hand osteoarthritis. - Ruiqi Wu; Qinglin Peng; Weiwei Wang; Jixian Zheng; Yi Zhou; Qipei Yang; Xuan Zhang; Hongyu Li; Lin Meng (PLoS ONE)
Objective Hand osteoarthritis poses a significant health challenge globally due to its increasing prevalence and the substantial burden on individuals and the society. In current clinical practice, treatment options for hand osteoarthritis encompass a range of approaches, including biological agents, antimetabolic drugs, neuromuscular blockers, anti-inflammatory drugs, hormone medications, pain relievers, new synergistic drugs, and other medications. Despite the diverse array of treatments, determining the optimal regimen remains elusive. This study seeks to conduct a network meta-analysis to assess the effectiveness and safety of various drug intervention measures in the treatment of hand osteoarthritis. The findings aim to provide evidence-based support for the clinical management of hand osteoarthritis. Methods We performed a comprehensive search across PubMed, Embase, Web of Science, and Cochrane Central Register of Controlled Trials was conducted until September 15th, 2022, to identify relevant randomized controlled trials. After meticulous screening and data extraction, the Cochrane Handbook's risk of bias assessment tool was applied to evaluate study quality. Data synthesis was carried out using Stata 15.1 software. Results 21 studies with data for 3965 patients were meta-analyzed, involving 20 distinct Western medicine agents. GCSB-5, a specific herbal complex that mainly regulate pain in hand osteoarthritis, showed the greatest reduction in pain [WMD = -13.00, 95% CI (-26.69, 0.69)]. CRx-102, s specific medication characterized by its significant effect for relieving joint stiffness symptoms, remarkably mitigated stiffness [WMD = -7.50, 95% CI (-8.90, -6.10)]. Chondroitin sulfate displayed the highest incidence of adverse events [RR = 0.26, 95% CI (0.06, 1.22)]. No substantial variation in functional index for hand osteoarthritis score improvement was identified between distinct agents and placebo. Conclusions In summary, GCSB-5 and CRx-102 exhibit efficacy in alleviating pain and stiffness in HOA, respectively. However, cautious interpretation of the results is advised. Tailored treatment decisions based on individual contexts are imperative.